English English - Raden Aditya Kusuma; Zainal Arif (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
ABSTRACT This study examines the integration of the Prophet's Sunnah with latest obstetric science through the lens of Maqāṣid al-Sharī'ah (the objectives of Islamic law). Using a qualitative approach with thematic analysis of hadith literature, medical evidence, and Islamic legal philosophy, the research reveals that the Prophet's teachings regarding maternal care from pregnancy (al-haml) through the Aqiqa ceremony (tahnik) embody fundamental principles of preserving life (ḥifẓ al-nafs), protecting lineage (ḥifẓ al-nasl), and promoting human dignity and intellect (ḥifẓ al-'aql). Modern obstetric practices—including prenatal monitoring, nutritional support, safe delivery protocols, and postnatal care—align remarkably well with these Prophetic teachings, demonstrating that Islamic principles and contemporary medical science are not merely compatible but genuinely complementary. The study concludes that integrating Sunnah-based guidance with evidence-based obstetric care provides a truly holistic approach that honors both the spiritual and physical dimensions of maternal and fetal well-being. Keywords: Prophet's Sunnah, obstetrics, Maqāṣid al-Sharī'ah, maternal care, tahnik